Synthesis and Characterization of Ag/TiO2 Nanoparticles using Mirabilis jalapa Plant Extract - Frida Octavia Purnomo; Sari Sekar Ningrum; Sadwika Najmi Kautsari (Syarif Hidayatullah State Islamic University, 2021)
Green synthesized nanomaterials have been widely developed because of their less toxicity, low energy process, environmentally friendly, effective, cheap, and pollution-free. Green synthesis of silver doped titanium dioxide nanoparticles (Ag/TiO2 NPs) was carried out using Mirabilis jalapa plant extract. The plant extract was used as a reducing agent. The functional groups, morphology, and crystalline structure of as-synthesized Ag/TiO2 NPs were investigated by FT-IR, FESEM, and XRD. Analysis by FESEM confirmed that the morphology of Ag/TiO2 NPs is spherical with an average size of 400 nm. Crystallite size for the Ag/TiO2 NPs was calculated by the Scherrer formula dan the average size found to be in the range of 15.72 nm. The result of XRD analysis showing the fcc structure for metallic silver and TiO2 particles in the anatase and rutile phases.